1986
DOI: 10.1177/027836498600400401
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multifingered Hands

Abstract: This paper discusses three fundamental problems relating to grasping and manipulating objects within an articulated, multifingered hand: determining how hard to squeeze an ob ject in order to ensure a secure grasp, determining the finger- joint motions required to produce a desired motion of the object, and determining the workspace of the hand. Squeezing the object, or the application of internal grasp forces, is reduced to a linear programming problem which considers friction and joint torque limit constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
308
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(310 citation statements)
references
References 1 publication
2
308
0
Order By: Relevance
“…The elements of an internal force vector cancel each other and, hence, do not contribute to the resultant force and moment acting on the object (Mason and Salisbury 1985;Kerr and Roth 1986;Yoshikawa and Nagai 1991;Murray et al 1994). It has been shown that during the performance, people exert internal moments on the object such that the moments of the normal and tangential forces (M n and M t , respectively) change in opposite directions in synchrony and cancel each other.…”
Section: Introductionmentioning
confidence: 99%
“…The elements of an internal force vector cancel each other and, hence, do not contribute to the resultant force and moment acting on the object (Mason and Salisbury 1985;Kerr and Roth 1986;Yoshikawa and Nagai 1991;Murray et al 1994). It has been shown that during the performance, people exert internal moments on the object such that the moments of the normal and tangential forces (M n and M t , respectively) change in opposite directions in synchrony and cancel each other.…”
Section: Introductionmentioning
confidence: 99%
“…Since the finger force has higher number of variables than the number of constraints in the equation of motion, there exist a lot of solutions, and it needs to be optimized [17], [18], [19]. The optimization process should take the frictional contact constraints into account, which is introduced in Section IV and Appendix, and here, we first determine the reaction force that can minimize the magnitude of the finger force.…”
Section: Optimization Policymentioning
confidence: 99%
“…The basic algorithms can be found in [17], [24], [25], while the main contribution of this paper is to adopt them to the multi-contact manipulation tasks under Reactional Internal Contact Hypothesis.…”
Section: Grasping Force Computationmentioning
confidence: 99%
“…To achieve a no-slippage contact grip, the following contact and friction constraints have to be satisfied (Kerr andRoth 1986, Montana 1992).…”
Section: Grasp Conditionsmentioning
confidence: 99%
“…Early attempts such as Kerr and Roth (1986), for example, proposed a linear programming approach to consider the intrinsic inequalities of the system which result from manipulatorobject contact criteria. Kumar and Waldron (1988) suggested using interaction forces to address this problem.…”
Section: Introductionmentioning
confidence: 99%